The role of nominal wages in trade and current account surpluses: An econometric analysis for Germany - Gustav A. Horn; Fabian Lindner; Sabine Stephan; Rudolf Zwiener (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2017)
A macroeconomically oriented wage policy in Germany in the years 2001 to 2015 would have led to a reduced growth of real net exports but would not have significantly reduced Germany's trade and current account surpluses. While real exports would have declined, higher export prices would have led to an increase in overall export receipts so that the current account surplus - denominated in euro terms - would scarcely have shrunk. Such a wage policy, however, would have increased domestic demand and would have influenced income distribution positively (an increase in the wage share). Such a policy would however, have improved the government's financial situation, thereby increasing its spending capacity. A combination of macroeconomic wage policy and a support by fiscal policy making use of the financial leeway created by higher wages would have decreased the nominal trade and current account balance to a greater degree than wage policy alone. Surpluses would mainly have been reduced through an increase in imports due to an improved domestic economic development. However, for the current account balance to be in line with EU rules, much stronger financial impulses would be needed. – – Eine makroökonomisch orientierte Lohnpolitik in Deutschland in den Jahren 2001 bis 2015 hätte bewirkt, dass die realen Nettoexporte deutlich weniger stark gestiegen wären. Aber sie hätte das Entstehen der deutschen Handels- und Leistungsbilanzüberschüsse nicht nennenswert gebremst. Zwar wäre das Exportvolumen zurückgegangen, die höheren Exportpreise hätten aber zu einem Anstieg der Exportumsätze geführt, so dass die nominal ausgewiesenen Leistungsbilanzüberschüsse kaum gesunken wären. Eine solche Lohnpolitik hätte aber stärkeres binnenwirtschaftliches Wachstum bewirkt und einen nennenswerten positiven Effekt auf die Verteilung (steigende Lohnquote) gehabt. Darüber hinaus hätte diese Lohnpolitik die Haushaltslage des Staates verbessert und damit die Voraussetzungen für finanzpolitische Impulse geschaffen. Eine Kombination aus makroökonomischer Lohnpolitik und unterstützender Finanzpolitik, die den durch die kräftigeren Lohnerhöhungen entstehenden finanzpolitischen Spielraum nutzt, senkt den nominalen Handels- und Leistungsbilanzüberschuss stärker als eine reine Lohnpolitik. Die Überschüsse würden sich vor allem wegen stärkerer Importe infolge einer besseren binnenwirtschaftlichen Entwicklung verringern. Für eine EU-konforme Reduzierung des Leistungsbilanzüberschusses müsste der Staat allerdings einen sehr viel stärkeren Finanzimpuls setzen.
urn:nbn:de:101:1-201707111512
Keywords: 330